La nao Santa María - Fernández Duro, Cesáreo, 1830-1908 (Barcelona : www.linkgua-digital.com, 2016)
Plans for reconstructing the Santa Maria and related items in celebration of the 400th anniversary of Columbus's voyage.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed June 8, 2018)
Keywords: Santa María (Ship : Replica); Columbus, Christopher; Sailing ships -- Spain; America -- Centennial celebrations, etc; Electronic books